2015
DOI: 10.1186/s12967-015-0445-9
|View full text |Cite
|
Sign up to set email alerts
|

Xanthine oxidase inhibition alleviates the cardiac complications of insulin resistance: effect on low grade inflammation and the angiotensin system

Abstract: BackgroundWe have previously shown that hyperuricemia plays an important role in the vascular complications of insulin resistance (IR). Here we investigated the effect of xanthine oxidase (XO) inhibition on the cardiac complications of IR.MethodsIR was induced in rats by a high fructose high fat diet for 12 weeks. Allopurinol, a standard XO inhibitor, was administered in the last 4 weeks before cardiac hemodynamics and electrocardiography, serum glucose, insulin, tumor necrosis factor alpha (TNFα), 8-isoprosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…In our previous studies, allopurinol ameliorated fructose-induced metabolic syndrome and protects tissue injury by inhibiting NLRP3 inflammasome activation and IL-1β production 39 40 . Recently, allopurinol is found to restore a high-fat and high-fructose diet-induced cardiomyocyte oxidative stress, inflammation and hypertrophy in mice 41 , and alleviates cardiac ischemia in insulin resistance through inhibiting low grade inflammation and angiotensin system in rats fed with a high fructose and fat diet 42 . Thus, the cardioprotective effects of cinnamaldehyde and allopurinol against cardiac inflammation may be involved in heart injury under fructose-induced oxidative stress, but the molecular mechanism has not been understood yet.…”
mentioning
confidence: 99%
“…In our previous studies, allopurinol ameliorated fructose-induced metabolic syndrome and protects tissue injury by inhibiting NLRP3 inflammasome activation and IL-1β production 39 40 . Recently, allopurinol is found to restore a high-fat and high-fructose diet-induced cardiomyocyte oxidative stress, inflammation and hypertrophy in mice 41 , and alleviates cardiac ischemia in insulin resistance through inhibiting low grade inflammation and angiotensin system in rats fed with a high fructose and fat diet 42 . Thus, the cardioprotective effects of cinnamaldehyde and allopurinol against cardiac inflammation may be involved in heart injury under fructose-induced oxidative stress, but the molecular mechanism has not been understood yet.…”
mentioning
confidence: 99%
“…Their study demonstrated that inhibition of XOD improved blood flow in sciatic and cervical nerve ganglion, thereby suggesting that upregulated XOD present in nerve microvasculature, including endothelium and perivascular space, can cause neurovascular dysfunction leading to diabetic neuropathy. Allopurinol also prevented cardiac ischemia and impaired relaxation in an experimental model of insulin resistance [34], normalized endothelial function in T2DM patients with mild hypertension [35], alleviated oxidative injury and improved cardiovascular functions in diabetics in several intervention studies [36], and acted antinociceptive against various noxious stimuli in mice [37]. On the other side, peripheral neuropathy can be a side effect of allopurinol treatment, and this drug failed to prevent the progression of DPN in type 1 diabetes mellitus patients with mild-to-moderate cardiovascular autonomic neuropathy [38].…”
Section: Discussionmentioning
confidence: 99%
“…Ingestion of 60% fructose for over 8 weeks (Behr‐Roussel et al. ), or 10% over 12 weeks (El‐Bassossy and Watson ), has been reported to increase 8‐isoprostane excretion, a marker for renal reactive oxygen species production. High salt diets have been shown to increase urinary nitric oxide excretion (Shultz and Tolins ).…”
Section: Introductionmentioning
confidence: 99%
“…There is substantial literature regarding nitric oxide deficiency and/or oxidative stress that may contribute to hypertension (Wilcox 2005). Ingestion of 60% fructose for over 8 weeks (Behr-Roussel et al 2008), or 10% over 12 weeks (El-Bassossy and Watson 2015), has been reported to increase 8-isoprostane excretion, a marker for renal reactive oxygen species production. High salt diets have been shown to increase urinary nitric oxide excretion (Shultz and Tolins 1993).…”
Section: Introductionmentioning
confidence: 99%